TANGGUNG JAWAB PELAKU USAHA TERHADAP PRODUK MAKANAN TANPA MENCANTUMKAN LABEL TANGGAL KADALUARSA (DI HOME INDUSTRY KECAMATAN BATANG TUAKA KABUPATEN INDRAGIRI HILIR) - M. Romy Suryanto; Maryati Bachtiar; Meriza Elpha Darnia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
The increasingly rapid development of technology is currently influencingproduction activities so that they are able to meet the increasing and diverseneeds of consumers. On the one hand, increasing the use of more advancedtechnology can benefit consumers because their needs will be easily met with avariety of choices. On the other hand, increasingly sophisticated technology doesnot always produce products that comply with safety standards that can beconsumed by consumers and often harms consumers. Like home industry businessactors engaged in buying and selling food products. Home industry businessactors sell food products that do not include expiration date labels in order tomake a profit by not providing clear information to consumers.This type of research can be classified as empirical legal research or whatis usually called sociological research. With the research location being at theFood and Drug Monitoring Center (Loka POM) and Home Industry, BatangTuaka District, Indragiri Hilir Regency, the population and sample are all partiesrelated to the problem under study. This research uses data sources in the form ofprimary data and secondary data, and data collection techniques are carried outby interviews.From the research results it can be concluded that. Firstly, as regulated inArticle 19 of the UUP.. Second, there are legal remedies that consumers can take,namely through litigation and non-litigation. The advice from the author is:Firstly, business actors in running their business should show good faith andprovide clear information regarding the goods and/or services being distributedand try to pay attention to consumer rights and obligations as business actors andthe need for additional human resources as needed to be able to improveperformance of the Food and Drug Monitoring Station. Second, consumers shouldbe more careful in purchasing and consuming food products to avoid danger.Keywords: Home Industry-Expiration Date-Responsibility.